On relaxation phenomena in a two-component plasma - Gorev, V.N.; Sokolovsky, A.I.; Chelbaevsky, Z.Yu. (Condensed Matter Physics, 2015)
The relaxation of the temperatures and velocities of the components of a quasi-equilibrium two-component homogeneous completely ionized plasma is investigated on the basis of a generalization of the Chapman--Enskog method applied to the Landau kinetic equation. The generalization is based on the functional hypothesis in order to account for the presence of kinetic modes of the system. In the approximation of a small difference of the component temperatures and velocities it is shown that relaxation really exists (the relaxation rates are positive). The proof is based on arguments that are valid for an arbitrary two-component system. The equations describing the temperature and velocity kinetic modes of the system are investigated in a perturbation theory in the square root of the small electron-to-ion mass ratio. The equations of each order of this perturbation theory are solved with the help of the Sonine polynomial expansion. Corrections to the known Landau results related to the distribution functions of the plasma and relaxation rates are obtained. The hydrodynamic theory based on these results should take into account a violation of local equilibrium in the presence of relaxation processes. Релаксацiя температур та швидкостей компонент квазiрiвноважної двокомпонентної повнiстю iонiзованої просторово-однорiдної плазми вивчається на основi узагальненого методу Чемпена-Енскога, застосованого до кiнетичного рiвняння Ландау. Узагальнення базується на iдеї функцiональної гiпотези Боголюбова з метою врахувати кiнетичнi моди системи. Показано, що в наближеннi малої рiзницi швидкостей та температур компонент системи релаксацiя дiйсно iснує (швидкостi релаксацiї додатнi). Доведення базується на аргументах, якi придатнi для довiльної двокомпонентної системи. Рiвняння, якi описують температурну та швидкiсну кiнетичну моди системи, дослiджуються у теорiї збурень за квадратним коренем малого вiдношення мас електрона та iона. Рiвняння будь-якого порядку в цiй теорiї збурень розв’язуються методом розвинення за полiномами Сонiна. Отримано корекцiї до вiдомих результатiв Ландау, стосовних функцiй розподiлу компонент плазми та швидкостей релаксацiї. Гiдродинамiчна теорiя, яка базується на цих результатах, повинна враховувати порушення локальної рiвноваги при наявностi релаксацiйних процесiв.